1999
DOI: 10.1152/ajpheart.1999.276.6.h1977
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of natriuretic peptide production by adult heart atria

Abstract: The cardiac polypeptide hormones atrial natriuretic factor (ANF) and brain natriuretic peptide (BNP) are synthesized and costored by atrial cardiocytes and share receptors and many biologic properties. Although some aspects of their synthesis and release are specific for each peptide, it is not clear whether they share intracellular sorting and secretory mechanisms. In the present work we take advantage of a stable isolated rat atrial preparation that allows, for the first time, long-term study of synthesis, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
26
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 27 publications
5
26
0
1
Order By: Relevance
“…7, where the classical constitutive, exocytotic, and constitutive-like release of ANF is shown. The latter type of release is the main vectorial transport pathway for stimulated ANF secretion, as demonstrated by previous investigations from this laboratory (37).…”
Section: Discussionsupporting
confidence: 70%
“…7, where the classical constitutive, exocytotic, and constitutive-like release of ANF is shown. The latter type of release is the main vectorial transport pathway for stimulated ANF secretion, as demonstrated by previous investigations from this laboratory (37).…”
Section: Discussionsupporting
confidence: 70%
“…21) as may be observed by increasing intraatrial distension resulting from a normal (e.g., head-out water immersion) or pathological increase in venous return (e.g., congestive heart failure; Refs. 25,28). Increased atrial distension by volume overload (VO) is also accompanied by an increased expression and secretion of both NPs.…”
mentioning
confidence: 99%
“…These investigations showed that whereas modulation of ventricular NP production by hormones in vivo resembles that which is obtained in vitro using cultures of neonatal cardiocytes, modulation of atrial NP production in vivo is largely independent of the endocrine factors so far tested. Atrial NP production, however, appears mainly determined by atrial wall stretch as modified by changes in blood volume (38) although in in vitro preparations such as the isolated atrial preparation (27), it is possible to modify atrial NP production with agents such as endothelin albeit at fairly high concentrations.…”
mentioning
confidence: 99%